Komunikasi Risiko Mitigasi Bencana Hidrometeorologi Dampak Kerusakan Lingkungan - Hidayat, Muhamad; Assegaf, Ahmad Hamudi (JURNAL KOMUNIKATIO, 2025)
The acceleration of global climate change accompanied by increased economic activity and human development, which tends to be exploitative of nature, such as deforestation, urbanization, and water, air, and land pollution, has caused an increase in the frequency, intensity, and impact of hydrometeorological disasters in Indonesia. The island of Bali, which has long been known for its natural beauty and cultural heritage, is also increasingly vulnerable to hydrometeorological natural disasters such as floods, droughts, and landslides. Based on disaster studies, hydrometeorological disasters are one of the most frequent disasters in Bali Province. This research aims to analyze risk communication for hydrometeorological disaster mitigation in Bali with the Crisis and Emergency Risk Communication (CERC) concept. The results are expected to provide new insights to the community and policymakers regarding risk and crisis communication strategies in disaster mitigation efforts. The method used in this research is qualitative, with a case study approach and data collection techniques through in-depth interviews and observation. Research location is in Bali Province, involving stakeholders such as the government institutions, professional associations, journalists, and business actors concerned about and involved in the disaster mitigation agenda in Bali Province. The research results show that collaboration between traditional elements, such as traditional leaders, religious leaders, and the government is important in increasing awareness and disaster mitigation capacity. Applying CERC principles has proven effective in strengthening community capacity and accelerating post-disaster recovery. The findings of this research show that inclusive risk communication based on local wisdom is the key to building community preparedness in anticipating and mitigating disasters.